PERTIMBANGAN HAKIM DALAM PUTUSAN KASASI NO. 2296 K/PID.SUS/2024 YANG MENYIMPANGI KETENTUAN PIDANA MINIMUM KHUSUS: PERTIMBANGAN HAKIM DALAM PUTUSAN KASASI NO. 2296 K/PID.SUS/2024 YANG MENYIMPANGI KETENTUAN PIDANA MINIMUM KHUSUS - Fahima Ramadani; Awaliah Awaliah; Hasnawati Hasnawati (Maleo Law Journal, 2026)
The purpose of this study is to analyze the basis of the Supreme Court judges' considerations in the deviation. This study uses a normative legal research method. The results of the study indicate that the Supreme Court corrected the judex facti decision by changing the application of the article from Article 114 paragraph (1) to Article 112 paragraph (1) of Law Number 35 of 2009 concerning Narcotics, the change in the application of the article by the Supreme Court was based on the failure to fulfill the elements of a sales intermediary due to the absence of relevant witnesses. However, in the aspect of criminalization, the Supreme Court imposed a prison sentence below the special minimum limit without adequate consideration of the reasons for the deviation, while the fine was still imposed according to the provisions of the law. This condition indicates a weak construction of the argumentation for punishment which has the potential to cause disparity in punishment, as well as create uncertainty in the application of the special minimum criminal provisions in judicial practice. Therefore, this study emphasizes the importance of comprehensive and argumentative considerations by judges in every deviation from the special minimum criminal provisions in order to maintain justice and legal certainty.